Rasio Konsentrasi Industri Pengolahan Terhadap Tenaga Kerja di Provinsi Bali - Achmad Andi Leanado; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the ratio of the concentration of the processing industry, labor absorption, and the value expenditure on labor in the province of bali. The data analysis method used in this analysis is the CR4 concentration analysis method. The data used is the analysis data on the number of large and medium processing industries, labor, and expenditure on labor in 2018 – 2021 obtained from the Central Statistic Agency (BPS) in the province of Bali. The result of this study indicate that : (1) In terms of CR4 analysis calculations, the concentration of the processing industry in the province Bali in 2018 – 2021 has a role in labor absorption. (2) In terms of CR4 analysis calculation, the concentration of the processing industry in province Bali in 2018 – 2021 has a role in the amound of expenditure given to labor. (3) In terms of CR4 analysis calculation, the concentration of the processing industry in the province Bali in 2021 has a role contributing to the PDRB in the province of Bali, as well as a comparison of the CR4 ratio in the province of Bali from 2018 – 2021.